Cover Image, Volume 59, Issue 7. Issue 7 (7th June 2020) - Mitchell, Elizabeth; Jindal, Sonali; Chan, Tiffany; Narasimhan, Jayasri; Sivagnanam, Shamilene; Gray, Elliot; Chang, Young Hwan; Weinmann, Sheila; Schedin, Pepper
Abstract : Cover Caption : The cover image is based on the Original Article Loss of myoepithelial calponin‐1 characterizes high risk ductal carcinoma in situ cases, which are further stratified by T cell composition by Pepper Schedin, Elliot Gray, Jayasri Narasimhan et al., https://doi.org/10.1002/mc.23171 .